1980
DOI: 10.1007/bf00015484
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemistry, destratification and nutrient budget of a lowland eutrophicated Malaysian reservoir and its limnological implications

Abstract: Subang Lake (3°1oN, tot°29'E) is a stratified lowland reservoir with a marked chemocline of some variables that probably contributes to a greater species diversity and vertical layering of plankton communities . Destratification occurs in the reservoir and is probably seasonal . Destratification results in toxic and deoxygenated waters as well as nutrient replenishment from the hypolimnion and could cause sudden mass fish and zooplankton mortality and consequent algal blooms . The nutrient budget study indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Sreenivasan (1964) have reported that the blooming of phytoplankton occurs in summer season. Arumugan and Furtado (1980) have observed similar pattern in some temperate and tropical reservoirs. Bharadwaja (1940) has also pointed out temperature and light as the factors responsible for the higher population of phytoplankton.…”
Section: Discussionsupporting
confidence: 74%
“…Sreenivasan (1964) have reported that the blooming of phytoplankton occurs in summer season. Arumugan and Furtado (1980) have observed similar pattern in some temperate and tropical reservoirs. Bharadwaja (1940) has also pointed out temperature and light as the factors responsible for the higher population of phytoplankton.…”
Section: Discussionsupporting
confidence: 74%
“…Significant (p < 0.05) gradual decrease in dissolved oxygen (DO) and DO (% Sat.) concentrations, along the water column from surface towards the bottom of the lake could be linked with higher photosynthetic activities at the surface and/or the higher decomposition processes at the bottom of the lake [22] [24] [25]. There was total oxygen depletion (anoxic condition) at the bottom of the lake in April 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, variable weather conditions can result in the lack of any definite seasonal pattern of thermal behaviour. Tropical reservoirs are particularly sensitive to changing weather conditions, not least to heavy rainfalls which can destratify the lake (Arumugam and Furtado, 1980) or even prevent stratification (Imevbore, 1967). Near the equator, stratification can be particularly weak, and mechanical mixing induced by wind regulates the mixing process.…”
Section: Reservoir Maturationmentioning
confidence: 99%